An interaction between Nrf2 polymorphisms and smoking status affects annual decline in FEV1: a longitudinal retrospective cohort study - Hirota Tomomitsu; Noguchi Emiko; Iijima Hiroaki; Naito Takashi; Kaneko Yoshiko; Sakamoto Tohru; Masuko Hironori; Tamari Mayumi; Hizawa Nobuyuki (BMC, 2011)
Abstract Background An Nrf2-dependent response is a central protective mechanism against oxidative stress. We propose that particular genetic variants of the Nrf2 gene may be associated with a rapid forced expiratory volume in one second (FEV1) decline induced by cigarette smoking. Methods We conducted a retrospective cohort study of 915 Japanese from a general population. Values of annual decline in FEV1 were computed for each individual using a linear mixed-effect model. Multiple clinical characteristics were assessed to identify associations with annual FEV1 decline. Tag single-nucleotide polymorphisms (SNPs) in the Nrf2 gene (rs2001350, rs6726395, rs1962142, rs2364722) and one functional SNP (rs6721961) in the Nrf2 promoter region were genotyped to assess interactions between the Nrf2 polymorphisms and smoking status on annual FEV1 decline. Results Annual FEV1 decline was associated with smoking behavior and inversely correlated with FEV1/FVC and FEV1 % predicted. The mean annual FEV1 declines in individuals with rs6726395 G/G, G/A, or A/A were 26.2, 22.3, and 20.8 mL/year, respectively, and differences in these means were statistically significant (pcorr = 0.016). We also found a significant interaction between rs6726395 genotype and smoking status on the FEV1 decline (p for interaction = 0.011). The haplotype rs2001350T/rs6726395A/rs1962142A/rs2364722A/rs6721961T was associated with lower annual decline in FEV1 (p = 0.004). Conclusions This study indicated that an Nrf2-dependent response to exogenous stimuli may affect annual FEV1 decline in the general population. It appears that the genetic influence of Nrf2 is modified by smoking status, suggesting the presence of a gene-environment interaction in accelerated decline in FEV1.